Analisis Kepuasan Nasabah Bank Syariah Indonesia: Studi Kasus Civitas Akademika Universitas Al- Amien Prenduan - Maulana, Ilham; Ismail, Moch.; Fachrudin, Fachrudin (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
This study aims to analyze the influence of service quality, product quality, and price on customer satisfaction at Bank Syariah Indonesia (BSI) among the academic community of Universitas Al-Amien Prenduan. Using survey methods and SEM-PLS analysis, the study involved a sample of academic community members who are BSI customers. The results indicate that price has a positive and highly significant effect (β=0.805, p0.01) on customer satisfaction, followed by product quality (β=0.203, p0.10). However, service quality did not show a significant effect. These findings highlight the importance of pricing strategies and product development in the context of Islamic banking within an academic environment. This study offers new insights into the factors affecting customer satisfaction in Islamic banks among academic communities and suggests directions for future research to explore the dynamics of customer satisfaction in this segment.